(untitled) (Nexo Revista Científica, 2021)
The level of deformation of the rock massif of a blasted slab must be planned in advance, depending on the required results of blasting. Thus the energy costs of barren rock overfilling as part of preparing for overburden excavation are inefficient. On the contrary, an increase in the blast energy spent on degrading and breaking the ore mass is an efficient measure of preparing for the excavation of mineral wealth. There are currently two methods used to determine the pre-destruction of a blasted rock massif. The first one is based on determining the number of strain waves passing through locations of borehole charges. However, this method fails to determine the preliminary rock destruction level. The second method is based on determining coefficients of the pre-destruction of a rock massif by these strain waves. The merit of this method is that it allows evaluating the quality pattern of the pre-destruction of a rock massif. The procedure of considering the fraction of energy of the strain waves, reflected by the shielding rock mass to the destructive amount of blasting charges and refracted to this destroyed rock, is proposed.